SUBJECTIVE DISPOSITION OF SMART ECONOMY - Iryna Uninets (Izdevnieciba "Baltija Publishing", 2021)
The article deals with the topical issue of modern economic development - the formation of Smart economy. The purpose of the article is to determine the subjective disposition and identify the characteristics of the main subjects of Smart economy. To achieve this goal, the article uses the method of system-structural analysis to identify the main subjects and characterize their properties in the context of the formation of Smart economy. The phenomenon of smart economy is associated with the growth of its reasonable nature, increasing attention to social and environmental issues, the priority of the principles of sustainable development. The changes taking place in the activity of the main actors (households, business, state) under the influence of the processes of digitalization, socialization, greening, urbanization, institutionalization are studied. Under the influence of digitalization, relations between actors in the process of economic activity are significantly accelerated, changed, and acquire new forms of manifestation. Sustainable development goals become a priority for any entity. New institutions and management mechanisms are being formed at various levels with the involvement of a wide range of new agents. The formation of smart economy is characterized by the following features: the spread of socially responsible business; penetration of smart technologies in all spheres of business, life and management; responsibility for the environment; priority of sustainable development goals in management at different levels; formation of smart living conditions for individuals and communities.